2001
DOI: 10.1007/s004170000238
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional analyses of diabetic macular edema by optical coherence tomography and multifocal electroretinograms

Abstract: The visual acuity was correlated significantly with morphological changes revealed by OCT and with multifocal ERGs. The combination of OCT and multifocal ERGs may provide objective criteria for the evaluation and assessment of diabetic macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 16 publications
9
71
1
Order By: Relevance
“…Although there are reports evaluating central macular function in subjects with diabetic macular oedema using microperimetry with scanning laser ophthalmoscope, 23 fundus-related microperimeter 24 and multifocal ERG, 25 correlation of decreased retinal sensitivity as a corollary to reduced retinal thickness (in participants with no clinical diabetic retinopathy or maculopathy), as measured on spectral domain OCT and MP has not been reported earlier.…”
Section: Discussionmentioning
confidence: 95%
“…Although there are reports evaluating central macular function in subjects with diabetic macular oedema using microperimetry with scanning laser ophthalmoscope, 23 fundus-related microperimeter 24 and multifocal ERG, 25 correlation of decreased retinal sensitivity as a corollary to reduced retinal thickness (in participants with no clinical diabetic retinopathy or maculopathy), as measured on spectral domain OCT and MP has not been reported earlier.…”
Section: Discussionmentioning
confidence: 95%
“…79,107,178,179,319 Foveal thickness as measured on optical coherence tomography (OCT) was found to be significantly correlated with mfERG amplitudes and implicit times. 178,319 Retinal locations with CSME had significant delays in mfERG implicit times with reduction in response amplitude. 79 The changes in implicit times were found to be more diffuse compared with amplitude changes and extended to areas without clinically manifesting macular edema.…”
Section: Diabetic Retinopathymentioning
confidence: 96%
“…Similar findings were observed in two other studies on DMO patients who had undergone vitrectomy with the creation of a posterior vitreous detachment. 11,12 We assessed the macular function by multifocal electroretinography (mfERG) and found that the electrical responses obtained from the macular area were also significantly correlated with the FT. 11 In that electrophysiological study, we examined the macular mfERG from the central 10 degrees along with the VA and OCT-determined FT. Although the VA improved significantly and the FT was reduced significantly at 6 months postoperatively, the amplitude of the mfERGs did not show any significant change, and only the peak latency of the macular response decreased significantly.…”
mentioning
confidence: 99%